Isolation and Characterization of Methicillin Resistant Staphylococcus aureus (MRSA) from milk samples - Jubeda Begum; Mir, Nasir Akbar (Indian Journal of Dairy Science, 2024)
This study reports the isolation and molecular characterization of methicillin-resistant S. aureus (MRSA) from sub-clinical mastitic milk samples of cows and does followed by the detection of multi-drug resistance profile of the isolates. The occurrence of MRSA was confirmed phenotypically as well as by molecular detection of the mecA gene. A total of 165 suspected mastitic milk samples were collected from cows (116) and does (49) in 2022 in Uttarakhand India. Out of 165 samples, 107 (64.8%) were positive for S. aureus (74 from cow and 32 from does samples) and 21 (19.6%) were positive for MRSA out of 107 (15 cow and 6 does samples). All the MRSA isolates were multidrug resistant. However, both MRSA and non-MRSA isolates were most sensitive to Chloramphenicol and complete resistance was observed against eight antibiotics including methicillin. The present study also revealed the resistance of MRSA isolates to antibiotics not used in veterinary medicine earlier. Our findings also highlights the detection of a significant percentage of MRSA in sub-clinical mastitic milk samples for the first time in the state of Uttarakhand, India; growing trends of multidrug resistance due to indiscriminate use of antibiotics and possible diffusion into the human food chain.